2022
DOI: 10.1002/eat.23754
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a digital tele‐guided intervention targeting components of the addictive appetite model for bulimia nervosa and binge‐eating disorder in Korea

Abstract: Objective: We aimed to evaluate the feasibility, acceptability, and potential impact of a tele-guided digital-based intervention based on the addictive appetite model of recurrent binge eating.Method: Female college students with bulimia nervosa (BN) or binge-eating disorder (BED) (n = 22) received a 6-week guided intervention targeting addictive processes and emotion regulation. The feasibility of the intervention was evaluated, and the outcomes were assessed at baseline, the end of the intervention, and 1-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A feasibility study assessing CRT found small within‐group effect sizes post‐intervention regarding neuropsychological test results (Rey‐Osterrieth complex figure test assessing central coherence and Brixton spatial anticipation test assessing set‐shifting), (Kuge et al, 2017). For BN/BED interventions, moderate to large effect sizes were found in all interventions on ED symptoms such as the frequency of binge‐purge symptoms (Hamatani et al, 2019; Kwag et al, 2022; Okamoto et al, 2017; Setsu et al, 2018). However, despite the moderate to large effect sizes, the results were not significant in Hamatani et al (2019), likely due to low power.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A feasibility study assessing CRT found small within‐group effect sizes post‐intervention regarding neuropsychological test results (Rey‐Osterrieth complex figure test assessing central coherence and Brixton spatial anticipation test assessing set‐shifting), (Kuge et al, 2017). For BN/BED interventions, moderate to large effect sizes were found in all interventions on ED symptoms such as the frequency of binge‐purge symptoms (Hamatani et al, 2019; Kwag et al, 2022; Okamoto et al, 2017; Setsu et al, 2018). However, despite the moderate to large effect sizes, the results were not significant in Hamatani et al (2019), likely due to low power.…”
Section: Resultsmentioning
confidence: 99%
“…For AN interventions, within-group, studies found significant improvements in ED psychopathology (Amemiya et al, 2012;Gu et al, 2021;Kim et al, 2019). However, in one of the RCTs which compared group CBT with treatment as usual (TAU), results in both groups were comparable (Gu et al, 2021) symptoms (Hamatani et al, 2019;Kwag et al, 2022;Okamoto et al, 2017;Setsu et al, 2018). However, despite the moderate to large effect sizes, the results were not significant in Hamatani et al (2019), likely due to low power.…”
Section: Rq3: Ed-related Outcomesmentioning
confidence: 99%
“…The usage of the self-help vodcasts was higher in patients with personality disorders in this study compared with the usage in previous eating disorders studies. 39 , 40 The use of the self-help videos varied across the participants. An interaction effect between time and group on reduced anxiety symptoms was found.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, poor diets dominated by HPFs are contributing to preventable deaths to a comparable degree as tobacco products [132]. Understanding whether addiction contributes to HPF intake may lead to new treatments, as preliminary research finds that behavioral and pharmacological interventions that target addictive mechanisms may reduce compulsive HPF intake [133,134]. Importantly, if the science supports that HPFs are not just unhealthy, but addictive, this challenges the assertion that excessive HPF intake is purely a matter of choice.…”
Section: Discussionmentioning
confidence: 99%